2020
DOI: 10.1186/s12889-019-7841-7
|View full text |Cite
|
Sign up to set email alerts
|

Social engagement pattern, health behaviors and subjective well-being of older adults: an international perspective using WHO-SAGE survey data

Abstract: Background: Social engagement forms the basis of social relationships by providing a sense of belonging, social identity, and fulfillment. Previous research demonstrates that social engagement was associated with positive health behaviors among older adults. However, the results have been different across health-related behaviors, and mostly based on data from high-income countries. For example, studies from the US and UK showed that social engagement was protective against smoking, while others found social e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 43 publications
2
41
1
1
Order By: Relevance
“…First, we discuss the aspect of behavior being guided by motivation. By participating in numerous social activities, participants perceived that they were in good health [43] and experienced positive emotions, such as higher self-esteem [44]. Their confidence was increased by their ability to take part in events and maintain their health despite their advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…First, we discuss the aspect of behavior being guided by motivation. By participating in numerous social activities, participants perceived that they were in good health [43] and experienced positive emotions, such as higher self-esteem [44]. Their confidence was increased by their ability to take part in events and maintain their health despite their advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross-sectional study among older Japanese people found that those who participated in social activities were also more physically active (Kikuchi et al, 2017). Luo and colleagues reported similar results in an international comparison of six countries (Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…Network structure determines the type and quantity of resources available. For instance, having a larger network and more contact with network ties offers access to more resources ( 5 ) and more opportunities for social engagement and cognitively stimulating interactions that in turn enhance well-being ( 6 ) . Similarly, having a diverse network offers more opportunities to compensate for network losses as well as to call on diverse sets of resources in response to specific social, emotional, and health-related needs ( 7 ) .…”
Section: Background and Objectivesmentioning
confidence: 99%